Correction: Signal transmission encryption based on dye-doped chiral liquid crystals via tunable and efficient circularly polarized luminescence. Issue 10 (9th May 2022) - Li, Chengxi; Yang, Xuefeng; Han, Jianlei; Sun, Wenjing; Duan, Pengfei
Abstract : Correction for 'Signal transmission encryption based on dye-doped chiral liquid crystals via tunable and efficient circularly polarized luminescence' by Chengxi Li et al., Mater. Adv., 2021, 2, 3851–3855, DOI: ; https://doi.org/10.1039/D1MA00368B .